CLIC recombination scheme for the low energy operation mode - Gerbershagen, A; Schulte, D; Burrows, P (2012)
The CLIC recombination scheme is a concept of multiplication of the drive beamfrequency in order to generate a 12 GHz RF wave for the main beam acceleration. CLIC isdesigned to be operated at nominal energy and in low energy modes. The low energy operationmodes require the train length to be increased by different factors in order to maintainthe same level of luminosity. Also the number of initial trains that are merged to formeach final train is changed. The combination scheme must be able to accommodate andrecombine both long and short trains for nominal and low energy CLIC operation modes. Therecombination hence becomes a non-trivial process and makes the correction of the errors inthe drive beam more challenging. The present paper describes in detail the recombinationprocess and its consequences. Copyright © 2012 by IEEE.